The Endophytic Bacteria, Salicylic Acid, and their Combination as Inducers of Rice Resistance Against Xanthomonas oryzae pv. oryzae - Christoffol Leiwakabessy; Meity Suradji Sinaga; Kikin H. Mutaqien; Trikoesoemaningtyas Trikoesoemaningtyas; Giyanto Giyanto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2018)
Bacterial leaf damage or blight brought by bacteria Xanthomonas oryzae pv. oryzae (X. oryzae pv. oryzae) is considered as an extremely serious disease of rice worldwide, including Indonesia. Induced resistance using chemical and biological agents was considered as a method to control the disease. The objectives of this research were to analyze of endophytic bacteria (Lysinibacillus sphaericus/L.sphaericus) and salicylic acid as the inducers of rice resistance against X. oryzae pv. oryzae. This study used three-factorial incompletely randomized designs to study the effect of endophytic bacteria and salicylic acid on three varieties of rice. The results of the study showed that endophytic bacteria and salicylic acid induced rice resistance to X. oryzae pv. oryzae. This endophytic bacterium was also able to increase the plant height (AUPHGC), the number of tillers (AUNTGC), and the number of productive tillers. The application of salicylic acid at the concentrations of 10 mM was able to suppress the BLB disease and increased the number of tillers and 1000-grain weight. The result of study showed that the endophytic bacteria and salicylic acid could induce resistance of rice varities against BLB disease and increased the number of productive tillers.